Identifying lifetime as one of the key parameters responsible for the low brightness of lanthanide-based OLEDs - Utochnikova, Valentina V; Aslandukov, Andrey N; Vashchenko, Andrey A; Goloveshkin, Alexander S; Alexandrov, Alexey A; Grzibovskis, Raitis; Bünzli, Jean-Claude G (Dalton transactions : an international journal of inorganic chemistry, 2021)
OLEDs based on lanthanide complexes have decisive optical advantages but are hampered by low brightness. Despite the efforts to optimize several parameters such as quantum yield and charge carrier mobility, there seems to be another key parameter that hinders their performances. Experimental data are therefore collected for mixed-ligand europium complexes with bathophenanthroline and different classes of anionic ligands and screened to identify the key parameter responsible for this situation, which turns out to be the long lifetime of their excited states. A broad literature search supports this conclusion, showing that lanthanide complexes are inferior to other classes of OLED emitters often because of their long lifetimes; furthermore, among a series of lanthanide complexes, the best results are achieved for those with the shortest lifetimes, even though they suffer from low quantum yields. Using red-emitting Eu 3+ complexes, the key factor curbing lanthanide-based OLED luminance was found, which is the lifetime of the excited state.